Artificial turf systems for sport surfaces: current knowledge and research needs - Fleming, P. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2011)
Artificial sport surfaces, for team outdoor sports, are growing in number in many sports including soccer (association football), rugby, hockey, and football (American and Australian). The science of their behaviour has, it is argued, been under-researched in comparison to the development of artificial turf products and also the development of many of the sports with respect to athleticism and advances in equipment such as footwear. This paper reviews artificial turf design requirements and behavioural aspects to develop the science, and draws from a range of up-to-date literature to identify the key principles of behaviour and gaps in knowledge. The relationship between the material types used in the substrate support and surface system (comprising some form of shockpad and turf, the turf infilled or unfilled) behaviour is demonstrated in regard to the key performance factors of player-surface interaction - for both impact and traction. The data demonstrate the relatively complex behaviour of surface systems, and highlight the pitfalls of current simple mechanical tests in relation to human loading. Degradation and the role of maintenance to sustain long-term performance are issues also highlighted and discussed. Surface safety is discussed through a short review of studies related to injury risk, albeit most were associated with the contrast between natural turf and artificial turf; however, there is clearly more research required in injury surveillance to include aspects of objective surface measurement. This paper additionally provides the reader with a state-of-the-knowledge review of where current thinking is now, and where future research is considered to be of merit, in developing sport surface science.